2020
DOI: 10.1155/2020/2147503
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Permeability Evolution and Its Formation Mechanism of Xiaojihan Aquifer Coal Seam under Plastic Flow

Abstract: Study on permeability evolution of an aquifer coal seam in Western China is of great significance for preventing water inrush disaster and realizing water-conserving coal mining. The permeability evolution of an aquifer coal seam is related to a loading path closely under plastic flow. In this work, permeability variations of the Xiaojihan water-bearing coal seam and Longde nonwater coal seam are researched using a transient method under plastic flow. The experiment results indicated the following: (1) Under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Mining of shallow coal seams in areas with scarce water resources and environmental problems inevitably causes the overlying rock subsidence and groundwater level drop, jeopardizing the fragile ecological balance [1][2][3]. In particular, this refers to the arid and semiarid regions of western China, for which the water-preserving mining seems to be the most lucrative solution [4][5][6][7]. Water-preserving mining is concerned with the protection of water resources throughout the process of mining.…”
Section: Introductionmentioning
confidence: 99%
“…Mining of shallow coal seams in areas with scarce water resources and environmental problems inevitably causes the overlying rock subsidence and groundwater level drop, jeopardizing the fragile ecological balance [1][2][3]. In particular, this refers to the arid and semiarid regions of western China, for which the water-preserving mining seems to be the most lucrative solution [4][5][6][7]. Water-preserving mining is concerned with the protection of water resources throughout the process of mining.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al established the model of the influence of creep deformation and matrix-fracture interaction on the permeability of deep coal and obtained that the permeability decreases with the decrease of pore pressure in the secondary stage and the initial stage of creep by using the fractional derivative transient pulse method and nonlinear least square method [26]. In order to study the permeability law of water-bearing coal seams under the condition of plastic flow, Guo et al used the transient method to study the permeability changes of water-bearing coal seams and water-free coal seams and concluded that the internal fracture closure rate of water-bearing coals is lower than that of water-free coals, which is conducive to water storage and transportation [27]. Qinghe et al studied the anisotropic permeability of different ranks of coal under the influence of CO2 adsorption and effective stress, conducted permeability tests under the conditions of cyclic loading and unloading and supercritical CO 2 , and concluded that the permeability of coal seams varies with coal ranks, and the permeability is anisotropic, showing that the permeability of parallel layers is greater than that of vertical layers [28].…”
Section: Introductionmentioning
confidence: 99%